Evaluasi Terhadap Penerimaan Pengguna Sistem Enterprises Resource Planning PT. Perkebunan Nusantara XI (Persero) Dengan Model Adapted UTAUT - Putri Wulandari; Niken Hendrakusma Wardani; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
This study aims to determine the factors that affect the acceptance of users of the Enterprises Resource Planning system at PT. Perkebunan Nusantara XI (Persero) using UTAUT Adapted model. The population of this study are employees of PT. Perkebunan Nusantara XI (Persero) which have the right of access to the system starting from procurement, production, distribution, sales, to human resources. The number of samples used in this study is 80 respondents. Research begins by evaluating the variables of the UTAUT model that are predicted to determine the factors of Enterprises Resource Planning system user acceptance, including Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Anxiety, Attitude, and Behavioral Intention. The measuremence model using PLS-SEM. The result shows is suitability of the model adopted in determining the acceptance factors of the Enterprises Resource Planning system user PT. Perkebunan Nusantara XI (Persero). The model can explain the effect of variance on Behavioral Intention of 70.9% and shows a significant relationship between each hypothesis. The adoption of this research model refers to the user research acceptance of the mandatory ERP system and focuses on the influence of direct relations of exogenous variables with attitude and intention factors behaving in ERP system user acceptance.